STUDI HUKUM ISLAM TERHADAP KEWARISAN MASYARAKAT ADAT SEMENDO KABUPATEN LAMPUNG BARAT DI ERA KONTEMPORER - Mukhlishin, A; Khotamin, Nur Alfi; Rohmawati, Ari; Ariyanto, Ariyanto (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Society of Semendo tribe follows matrilineal kinship system within major legacy. It means that the elder daughter is the only heir in legacy practice which is called Tunggu Tubang. It is a significant case for studies on Islamic law, especially the legacy law system of Islam. In Islamic legacy system, the distribution always sets out justice principle, equivalence, and prosperity in its implementation. Therefore, the focus of this study is the analysis of Islamic law toward the legacy in society of Semendo at West Lampung in contemporary era. This research is field research by using qualitative approach. The finding shows that philosophically the legacy system of Semendo tradition in perspective of Islamic law (the legacy law of Islam) is not in contradictory with the basics of prosperity and ushul fiqh of â€œurfâ€ (tradition). Furthermore, in the contemporary era at West Lampung regency, it indicates displacement of existing values in Semendo society. The major legacy system gradually changes into individual legacy system that is parental as an effect of modernization and wider society network.